Gratitude and Life Satisfaction as Predictors of Organizational Commitment in Anganwadi Workers - Sood, Sarita; Bakhshi, Arti; Singh, Komal (Prabandhan: Indian Journal of Management, 2015)
The present study explored the relationship between gratitude, life satisfaction, and organizational commitment by considering a sample of 110 Anganwadi workers from Anganwadi Centers, Department of Social Work, Jammu. Simple random sampling was employed for the collection of data. Correlational analysis of the data indicated that gratitude, life satisfaction, and organizational commitment are significantly correlated. Regression analysis revealed that gratitude is the predictor of organizational commitment and life satisfaction promotes continuance commitment. Theoretical and practical implications of the results were also discussed.